The house of pride, and other tales of Hawaii - London, Jack, 1876-1916 (Salt Lake City, UT : Project Gutenberg, 2000)
"The House of Pride, and Other Tales of Hawaii" by Jack London is a collection of stories written in the early 20th century. The tales delve into the lives of individuals living in Hawaii, exploring themes of identity, class, and the impacts of colonialism. The characters grapple with their desires, societal expectations, and the complexities of their connections to both place and family. The opening of the first story introduces Percival Ford, a wealthy and self-proclaimed spiritual aristocrat, attending a farewell dance for army personnel about to leave for Alaska. Despite his status, Ford feels out of place among the officers and their wives, manifesting a sense of disapproval towards their carefree lifestyles. As he reflects on his austere upbringing under the influence of his father, the esteemed Isaac Ford, Percival grapples with his own insecurities and moral viewpoints. The complex relationship with his half-brother Joe Garland, who embodies the carefree spirit Ford despises, becomes central to the narrative. This initial encounter sets the stage for a deeper exploration of family ties, identity, and societal roles as the story unfolds. (This is an automatically generated summary.)
The house of pride -- Koolau the leper -- Good-by, Jack -- Aloha oe -- Chun Ah Chun -- The sheriff of Kona -- Jack London.
Release date is 2000-12-01
Transcribed from the 1919 Mills & Boon edition by David Price
Keywords: Short stories, American; Hawaii -- Social life and customs -- Fiction